Cell–cell interaction in the heart via Wnt/β-catenin pathway after cardiac injury. (3rd March 2014) - Deb, Arjun
Abstract: The adult mammalian heart predominantly comprises myocytes, fibroblasts, endothelial cells, smooth muscle cells, and epicardial cells arranged in a precise three-dimensional framework. Following cardiac injury, the spatial arrangement of cells is disrupted as different populations of cells are recruited to the heart in a temporally regulated manner. The alteration of the cellular composition of the heart after cardiac injury thus enables different phenotypes of cells to interact with each other in a spatio-temporal-dependent manner. It can be argued that the integrated study of such cellular interactions rather than the examination of single populations of cells can provide more insights into the biology of cardiac repair especially at an organ-wide level. Many signalling systems undoubtedly mediate such cross talk between cells after cardiac injury. The Wnt/β-catenin system plays an important role during cardiac development and disease. Here, we describe how cell populations in the heart after cardiac injury mediate their interactions via the Wnt/β-catenin pathway, determine how such interactions can affect a cardiac repair response and finally suggest an integrated approach to study cardiac cellular interactions.